The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/pola.20481
|View full text |Cite
|
Sign up to set email alerts
|

Non‐transition metal‐catalyzed living radical polymerization of vinyl chloride initiated with iodoform in water at 25 °C

Abstract: Non‐transition metal‐catalyzed living radical polymerization (LRP) of vinyl chloride (VC) in water at 25–35 °C is reported. This polymerization is initiated with iodoform and catalyzed by Na2S2O4. In water, S2O dissociates into SO that mediates the initiation and reactivation steps via a single electron transfer (SET) mechanism. The exchange between dormant and active propagating species also includes the degenerative chain transfer to dormant species (DT). In addition, the SO2 released from SO during the SET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
201
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(215 citation statements)
references
References 56 publications
14
201
0
Order By: Relevance
“…[44][45][46][47] In light of the theory proposed here it may be as a result of the reduced transient radical lifetime that defects, which for vinyl chloride polymerization are largely caused by transfer to polymer, are reduced. In addition, similar polymerizations conducted in aqueous media suggested that chain transfer to the poly(vinyl alcohol) stabilizer employed does not occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] In light of the theory proposed here it may be as a result of the reduced transient radical lifetime that defects, which for vinyl chloride polymerization are largely caused by transfer to polymer, are reduced. In addition, similar polymerizations conducted in aqueous media suggested that chain transfer to the poly(vinyl alcohol) stabilizer employed does not occur.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, similar polymerizations conducted in aqueous media suggested that chain transfer to the poly(vinyl alcohol) stabilizer employed does not occur. 47,48 Given that chain transfer to PVA in conventional radical polymerization of PVC is extensive and leads to a characteristic skin of the resulting particles, it is clear that the imposition of controlled polymerization conditions significantly diminishes the extent of transfer in this case. 48 Extending further it has been shown that in general, copper(0) mediated polymerization has excellent end group fidelity in comparison to other atom transfer processes.…”
Section: Resultsmentioning
confidence: 99%
“…Because sodium dithionate is not able to form growing radicals and start the polymerization, as happens for example when peroxides are used (common DCT systems), a better control over the polymerization is achieved. The outstanding structural properties of the PVC that resulted from this LRP method were already assessed by nuclear magnetic resonance 10 (NMR) carried out to very lowmolecular weight PVC samples that could not be prepared without a living mechanism. The new PVC-LRP prepared by SET-DTLRP demonstrated to have high crystallinity, 10 to be free of structural defects, 9,10 and to require more than twice the time to burn completely in the discoloration tests by using the standard discoloration tests used in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nevertheless, the stringent conditions associated to some of these methods have limited the perspectives for widespread of commercial products. After several years of the development, Percec et al discovered a new strategy to polymerize-activated [6][7][8] and nonactivated monomers, [9][10][11] under controlled/ living mechanism in aqueous medium. In addition, this method requires only industrially consumed compounds and lead to a polymer that does not need to be purified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation